Ionizing Radiation Curtails Immunosuppressive Effects From Cancer-Associated Fibroblasts on Dendritic Cells - Berzaghi, Rodrigo; Tornaas, Stian; Lode, Kristin; Hellevik, Turid; Martinez-Zubiaurre, Inigo (Frontiers in Immunology, 2021)
Cancer-associated fibroblasts (CAFs) participate actively in tumor development and affect treatment responses, by among other mechanisms, promoting an immunosuppressive tumor microenvironment. In contrast to normal fibroblasts, reactive CAFs secrete a myriad of immunomodulatory soluble factors at high levels, i.e. growth factors, cytokines, and chemokines, which directly influence tumor immunity and inflammation. CAFs have been identified as important players in tumor radioresistance. However, knowledge on the immunomodulatory functions of CAFs during/after radiotherapy is still lacking. In this study, we investigated the effects of ionizing radiation on CAF-mediated regulation of dendritic cells (DCs). CAFs were obtained from freshly operated lung cancer tissues, while DCs were procured from peripheral blood of healthy donors. Experimental settings comprised both co-cultures and incubations with conditioned medium from control and irradiated CAFs. Functional assays to study DC differentiation/activation consisted on cytokine release, expression of cell-surface markers, antigen uptake, migration rates, T cell priming, and DC-signaling analysis. We demonstrate that CAFs induce a tolerogenic phenotype in DCs by promoting down-regulation of: i) signature DC markers (CD14, CD1a, CD209); ii) activation markers (CD80, CD86, CD40, and HLA-DR) and iii) functional properties (migration, antigen uptake, and CD4+ T cell priming). Notably, some of these effects were lost in conditioned medium from CAFs irradiated at fractionated medium-dose regimens (3x6 Gy). However, the expression of relevant CAF-derived regulatory agents like thymic stromal lymphopoietin (TSLP) or tryptophan 2,3-dioxygenase (TDO2) was unchanged upon irradiation. This study demonstrates that CAFs interfere with DC immune functions and unveil that certain radiation regimens may reverse CAF-mediated immunosuppressive effects.